1976
DOI: 10.1073/pnas.73.5.1664
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell division in Saccharomyces cerevisiae by methionyl-tRNA.

Abstract: We suggest that two events are necessary for an asynchronous population of cells to undergo arrest in the GI phase of the cell cycle upon nutrient starvation. First, passage through GI must be prevented by a deficiency of some metabolic intermediate. Since this intermediate may act indirectly to arrest division, we designate it the "signal." We have found three conditions under which Saccharomyces cerevisiae cells arrest division in GI: sulfate starvation of a prototroph, methionine starvation of an auxotroph,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 29 publications
9
96
0
Order By: Relevance
“…The intimate relationship between protein biosynthesis and cell cycle progression through G1 that we observed is consistent with previous observations linking protein synthesis with G1 transit (Unger and Hartwell, 1976;Bedard et al, 1981;Moreno and Nurse, 1994), with connections between ribosome biogenesis and cell size regulation at Start (Jorgensen et al, 2002(Jorgensen et al, , 2004, and with links between translation rate and G1 (Polymenis and Schmidt, 1997) and provides a global view of cellular processes that contribute to passage through the cell cycle commitment point in G1, Start. There is concordance between our G1 data and that derived from cell cycle screening of Drosophila cells after gene product depletion by RNAi (Bjorklund et al, 2006) in that both screens show clear involvement of protein biosynthesis pathways in G1 transit.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The intimate relationship between protein biosynthesis and cell cycle progression through G1 that we observed is consistent with previous observations linking protein synthesis with G1 transit (Unger and Hartwell, 1976;Bedard et al, 1981;Moreno and Nurse, 1994), with connections between ribosome biogenesis and cell size regulation at Start (Jorgensen et al, 2002(Jorgensen et al, , 2004, and with links between translation rate and G1 (Polymenis and Schmidt, 1997) and provides a global view of cellular processes that contribute to passage through the cell cycle commitment point in G1, Start. There is concordance between our G1 data and that derived from cell cycle screening of Drosophila cells after gene product depletion by RNAi (Bjorklund et al, 2006) in that both screens show clear involvement of protein biosynthesis pathways in G1 transit.…”
Section: Discussionsupporting
confidence: 78%
“…For example, depletion of SSU processome proteins leads to G1 arrest due to lack of ribosomes (Bernstein and Baserga, 2004), as does depletion of the 20S pre-rRNA maturation factor Rio1 (Angermayr et al, 2002). Similarly, tRNA charging has long been linked to G1 transit as a number of mutants in tRNA synthetases arrest in G1 (Unger and Hartwell, 1976;Bedard et al, 1981). Consistent with existing links between protein synthesis and G1 transit, our data indicate that the most dramatic restriction on a cell's ability to progress past the cell cycle commitment point in G1 (known as Start in yeast) is the capacity for protein synthesis, as inhibiting protein synthesis by a range of different means caused accumulation of cells in G1.…”
Section: G1 Phasementioning
confidence: 99%
“…Alternatively, yeast could be sensing a balance between new 60S and 40S subunit synthesis or decreases in new 40S subunit synthesis. In addition, we cannot exclude the possibility that yeast sense small changes in translation that are undetectable with our assays because changes in translation can clearly influence Start (Unger and Hartwell, 1976;Moore, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomena exist in a wide variety of organisms including bacteria, fission yeast, and avian erythroblasts (Donachie, 1968;Hartwell et al, 1974;Johnston et al, 1977;Nurse and Thuriaux, 1977;Dolznig et al, 2004). Arrest at Start in yeast can be caused by nutrient deprivation, mating pheromones, or translation defects (Unger and Hartwell, 1976;Hartwell and Unger, 1977;Johnston et al, 1977). It is not known whether the critical cell size setpoint sensed corresponds to cell volume, protein content per cell, RNA content per cell, or rates of protein or ribosome synthesis (Jorgensen and Tyers, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, the pool of available cellular methionine is smaller than virtually any other amino acid; thus, methionine is likely to be limiting (Jones and Fink, 1982). Indeed, Unger and Hartwell (1976) noted that starvation for sulfur or for methionine effectively causes G1 arrest, suggesting that cell cycle progression is particularly sensitive to the availability of methionine. They also found that a temperaturesensitive allele of methionine tRNA synthetase causes G1 arrest, even in the presence of methionine.…”
Section: Methionine Biosynthesismentioning
confidence: 99%